MENGUNGKAP KENDALA PENERAPAN SAK EMKM PADA UMKM DI KECAMATAN SANDUBAYA - Miftahatul Khairani Ulfa; Halpiah, Halpiah; Hery Astika Putra (Nusantara Hasana Journal, 2024)
This research is entitled “Uncover The Obstacles In Implementing SAK EMKM At UMKM In Sandubaya Sub-District”. The purpose of this research is to find out obstacles faced by UMKM actors in Sandubaya sub-district in implementing SAK EMKM. This research is a qualitative research with a narrative approach. The type of this research is used field research. Key informants in this research were the owners of UMKM in Sandubaya sub-district, especially UMKM of Bread UMKM Babakan Village, Tofu UMKM Abiantubuh Village, and Fried Onion UMKM Mandalika Village which is the focus of research. The results of this research indicate that some of the obstacles that are the cause of not implementing SAK EMKM at UMKM in Sandubaya sub-district are, lack of accounting knowledge of UMKM actors, improper perception regarding the recording of financial statements, there is no socialization about SAK EMKM to UMKM actors, absence competent of human resources in accounting and management, lack of educational background, average age fourty years old and above, and also the absence of regulations from the government,as well as to avoid taxes.